Cardiac performance after an endurance open water swimming race - Martinez, V.; Sanz-de la Garza, M.; Grazioli, G.; Bijnens, B. H.; Trapé, J.; Garcia, G.; Corzan, P.; Clemente, A.; González, B.; Sitges, M. (European Journal of Applied Physiology, 2019)
Purpose: Endurance exercise competitions have shown a transient negative effect on global right ventricular (RV) performance. Most published studies are based on terrestrial sports. The aim of our study was to evaluate the cardiac effects after an open water swimming race. Methods: We evaluated 33 healthy swimmers (mean age 40.9 ± 7.2) participating in a 9.5 km open water swimming race. All subjects underwent a standard transthoracic echocardiography including an evaluation of dimensions and myocardial ventricular deformation. Echocardiography was performed 24 h before and within the first hour of arrival at the finish line. Cardiac troponin I (cTn I), NT-ProBNP and leukocytes were also evaluated. Results: No changes in left ventricle (LV) ejection fraction or LV global longitudinal strain were observed. A significant increase in RV end-diastolic area (RVEDA) was noted after the race (RVEDA at baseline 15.12 ± 1.86; RVEDA after race 16.06 ± 2.27, p < 0.05), but no changes were seen in RV fractional area change or RV global longitudinal strain. Cardiac biomarkers and leukocytes significantly increased. No association was detected between the increase in cTn I or NT-proBNP and the RV acute dilatation or LV performance. A significant association was observed between cTn I and leukocytes (r = 0.375, p < 0.05). Conclusions: An acute RV dilatation but without an impairment in RV deformation was observed after participating in an endurance swimming race. The correlation between the increase in cTn I and leukocytes, but not with ventricular performance, may support the hypothesis of an exercise-induced increase in myocardial sarcolemmal permeability due to an inflammatory response rather than myocardial injury.